Effects of dissolved black carbon bound with goethite on physicochemical properties and adsorption capacity for imidacloprid: Adsorption versus coprecipitation - Zhang, Peng; Ma, Mingming; Meng, Xingying; Shao, Yifei; Liu, Aiju (Frontiers in Environmental Science, 2022)
Dissolved black carbon (DBC) is an important component of natural dissolved organic matter and can bind to iron minerals to form DBC-mineral complexes by adsorption and coprecipitation. However, reports regarding the difference in physicochemical properties between adsorbed and coprecipitated DBC-mineral complexes and their sorption capacity for polar organic pollutants are limited. Herein, goethite (Gt) and the adsorbed and coprecipitated complexes of DBC with Gt (SGt-DBC and CGt-DBC) were prepared, and their physicochemical properties and adsorption capacity for polar imidacloprid (IMI) were determined. The results showed that DBC could efficiently bind to Gt by coprecipitation or adsorption, leading to the aggregation of Gt particles, decreasing SSA, and increasing microporous volume, O-containing functional groups and negative charges. A greater effect was observed in CGt-DBC samples than SGt-DBC samples. CGt-DBC samples could more efficiently adsorb IMI than SGt-DBC samples, and CGt-DBC samples obtained the greatest Qmax with 68.4 mg/kg. The sorption mechanisms mainly involved hydrophobic partitioning, H-bonding, cation-π and p/π-π electron donor-acceptor interactions and electrostatic interactions. Additionally, the greater solution pH and Na+ concentration facilitated IMI adsorption on Gt and Gt-DBC samples; however, the Ca2+ solution obtained the opposite result. This effect on IMI adsorption was more pronounced for CGt-DBC samples. Therefore, the findings of this study provide a deep understanding of the interactions between Gt and DBC by adsorption and coprecipitation and their effect on the sorption of organic pollutants in natural soil and water environments.